EUTHANASIA AND HUMAN RIGHT TO LIFE IN INTERNATIONAL AND NATIONAL LAW - Baksheev, Andrei; Turchina, Zhanna; Gusarenko, Victoria; Rakhinsky, Dmitry; Rukavitsyna, Elena; Bershadskaja, Svetlana (Revista Inclusiones, 2020)
This article examines the problems of legal regulations for euthanasia in national and international law and legislation. The article aims to distinguish between murder and euthanasia in the Criminal code and investigate the possibility of euthanasia legalizing. Approach to euthanasia among lawmakers and law scholars differs; a uniform approach to its legalization has not yet been developed. However, at the present stage, due to its moral meaning, the legalization of euthanasia continues to be pertinent and relevant. A number of countries has already legalized euthanasia. By focusing on the concept and forms of euthanasia, the article considers the legal regulations for euthanasia in the Netherlands, Belgium and the USA. The article shows that our contemporary world is becoming favorable for moral and psychological acceptance of euthanasia. The article investigates the main trends of scientific research, which are characterized by growing attention to the problem of legalizing euthanasia. Due to its legal, medical, religious and moral aspects, the problem of legalization of euthanasia is complex. The article demonstrates the positions of supporters and opponents of euthanasia. Altogether, the article argues that in current situation acceptance of euthanasia in the Russian Federation, due to the moral and ethical views prevailing in the society, has not yet gained the support; however, mitigation of penalty for such an act in the penal code is necessary.